The impact of strength training on the improvement of jumping ability and selected power parameters of the lower limbs in soccer players - Fischerova, P.; Nitychoruk, M.; Smolka, W.; Zak, M.; Golas, A.; Maszczyk, A. (Baltic Journal of Health and Physical Activity, 2021)
Introduction: The aim of the study was to compare the impact of a 6-week program combined with football training and strength training on strength and power parameters in highly trained soccer players. It was hypothesized that 6 weeks would be enough for the experimental group to improve their jumping ability and pushing power.